Peran Manajemen Berbasis Sekolah dalam Peningkatan Kepuasan Stakeholder Eksternal di SMK Darur Roja Cinere Depok - Suhaedi, Ukat (Indonesia Economic Journal, 2025)
This study explores the role of School-Based Management (SBM) in enhancing external stakeholder satisfaction at SMK Darur Roja Cinere Depok, a vocational high school in Indonesia. Employing a qualitative descriptive approach, the research examines School-Based Management implementation through autonomy, community participation, and accountability in addressing expectations from parents, industry partners, and local communities. Findings reveal how School-Based Management fosters adaptive vocational education amid urban challenges, highlighting leadership dynamics and relational synergies that build school legitimacy. Theoretical integration of School-Based Management principles and stakeholder satisfaction theory underscores the need for contextual strategies in private vocational schools. The study offers insights for optimizing School-Based Management to strengthen vocational education competitiveness in Indonesia.